Trigonometric identities are true for all admissible values of the angle involved. There are some trigonometric identities which satisfy the given additional conditions. Such identities are called conditional trigonometric identities.
Example 1 :
If A + B + C = π/2, prove that
sin2A + sin2B + sin2C = 4cosAcosBcosC
Solution :
sin2A + sin2B + sin2C :
= 2sin(A + B)cos(A - B) + sin2C
= 2sin(90 - C)cos(A - B) + 2sinCcosC
= 2cosCcos(A - B) + 2sinCcosC
= 2cosC[cos(A - B) + sinC]
= 2cosC[cos(A - B) + sin(90 - (A + B)]
= 2cosC[cos(A - B) + cos(A + B)]
= 2cosC[2cosAcos(-B)]
= 2cosC[2cosAcosB]
= 4cosAcosBcosC
Example 2 :
If A + B + C = π/2, prove that
cos2A + cos2B + cos2C = 1 + 4sinAsinBcosC
Solution :
cos2A + cos2B + cos2C :
Use the identity of (cosC + cosD) for cos2A + cos2B.
= 2cos(A + B)cos(A - B) + cos2C
= 2cos(90 - C)cos(A - B) + 1 - 2sin2C
= 2sinCcos(A - B) + 1 - 2sin2C
= 1 + 2sinC[cos(A - B) - sinC]
= 1 + 2sinC[cos(A - B) - sin(90 - (A + B)]
= 1 + 2sinC[cos(A - B) - cos(A + B)]
= 1 + 2sinC[-2sinAsin(-B)]
= 1 + 2sinC[2sinAsinB]
= 1 + 4sinAsinBsinC
Example 3 :
If triangle ABC is a right triangle and ∠A = π/2, then prove that
(i) cos2B + cos2C = 1
(ii) sin2B + sin2C = 1
(iii) cosB - cosC = -1 + 2√2cos(B/2)sin(C/2)
Solution :
(i) cos2 B + cos2 C = 1 :
In the right triangle ABC above,
cosθ = Adjacent side/Hypotenuse
cosB = AB/BC
cosC = AC/BC
cos2B + cos2C = (AB/BC)2 + (AC/BC)2
= (AB2 + AC2)/BC2
= BC2/BC2
= 1
(ii) sin2 B + sin2 C = 1 :
In the right triangle ABC above,
sinθ = Opposite side/Hypotenuse
sinB = AC/BC
sinC = AB/BC
sin2B + sin2C = (AC/BC)2 + (AB/BC)2
= AC2/BC2 + (AB2/BC2)
= (AC2 + AB2)/BC2
= BC2/BC2
= 1
(iii) cosB − cosC = -1 + 2 √2 cos B/2 sin C/2 :
cosB - cosC = 2cos2B - 1 - cosC
= -1 + 2cos2B - cosC ----(1)
In the triangle ABC above,
A + B + C = π
It is given that A = π/2. Then,
B + C = π/2
C = π/2 - B
Substitute C = π/2 - B in (1).
= -1 + 2cos2(B/2) - cos(π/2 - B)
= -1 + 2cos2(B/2) - sinB
= -1 + 2cos2(B/2) - 2sin(B/2)cos(B/2)
= -1 + 2cos(B/2)(cos(B/2) - sin(B/2))
B = π/2 - C ----> B/2 = π/4 - C/2
= -1 + 2cos(B/2)[cos(π/4 - C/2) - sin(π/4 - C/2)]
= -1 + 2cos(B/2)[cos(π/4 - C/2) - cos(π/2 - (π/4 - C/2))]
= -1 + 2cos(B/2)[cos(π/4 - C/2) - cos(π/4 + C/2)]
= -1 + 2cos(B/2)[-2sin(π/4)sin(-C/2)]
= -1 + 2cos(B/2)[2(1/√2)sin(C/2)]
= -1 + 2√2cos(B/2)sin(C/2)
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Feb 12, 25 08:14 AM
Feb 12, 25 08:11 AM
Feb 11, 25 11:15 AM